2015
DOI: 10.1002/bdra.23374
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis and young mothers: What makes them different from other mothers of the same age?

Abstract: A previous pregnancy loss was identified as the main risk factor for gastroschisis, while an increased use of sex hormones, perhaps related to the previous loss, could trigger a disruptive mechanism, due to their thrombophilic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…In a previous study (Rittler et al, ), we showed that a history of miscarriages was the main risk factor for gastroschisis. To our knowledge, an association between gastroschisis and pregnancy losses has only been mentioned by Getz et al ().…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In a previous study (Rittler et al, ), we showed that a history of miscarriages was the main risk factor for gastroschisis. To our knowledge, an association between gastroschisis and pregnancy losses has only been mentioned by Getz et al ().…”
Section: Discussionmentioning
confidence: 71%
“…They found that the risk factor was the short interval and the risk increased if the previous pregnancy ended in a miscarriage. On the contrary, in the study of Rittler et al () the identified risk factor was the miscarriage, regardless of the inter‐pregnancy interval.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, among multiparous and multigravida mothers, a change in paternity since the previous pregnancy has been associated with gastroschisis (5). Studies have also indicated possible age-specific associations between gastroschisis and prior pregnancy loss (8), as well as with certain infections (9). The findings in this report are subject to at least three limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although young maternal age has been identified as a risk factor for G, pregnancy loss and Chlamydia exposure in young women (16 -25 years old) seem to be risk factors for G (p < 0.002) [7] [8]. Despite the unknown etiology mechanism of formation of paraumbilical congenital defect in G, some authors suggest that the defect might occur through regression or precocious lesion of one of the omphalomesenteric arteries in the embryonic phase [9] through genetic teratogenic alterations and/or drugs, such as acetylsalicylic acid, pseudoephedrine, and acetaminophen and smoking habit would also be involved in its etiology [10].…”
Section: Introductionmentioning
confidence: 97%